2013
DOI: 10.1177/0269215513486497
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effect of an ankle-foot orthosis on gait biomechanics after stroke

Abstract: An ankle-foot orthosis can improve the ankle and knee kinematics, kinetics and energy cost of walking in stroke survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 30 publications
(136 reference statements)
7
125
2
1
Order By: Relevance
“…659 A recent meta-analysis and systematic review suggested the potential mechanism(s) associated with the above effects by demonstrating a positive effect of an AFO on ankle kinematics, knee kinematics in stance phase, kinetics, and energy cost. 658 Two RCTs 763,764 showed that after 3 months of AFO use, AFO users had better mobility while wearing the AFO. One small RCT 764 found that although a dynamic hinged AFO improved ambulatory function over a standard AFO, it induced some dependence; the standard AFO group performed better after 3 months of use when walking without any orthosis.…”
Section: Level Of Evidencementioning
confidence: 99%
“…659 A recent meta-analysis and systematic review suggested the potential mechanism(s) associated with the above effects by demonstrating a positive effect of an AFO on ankle kinematics, knee kinematics in stance phase, kinetics, and energy cost. 658 Two RCTs 763,764 showed that after 3 months of AFO use, AFO users had better mobility while wearing the AFO. One small RCT 764 found that although a dynamic hinged AFO improved ambulatory function over a standard AFO, it induced some dependence; the standard AFO group performed better after 3 months of use when walking without any orthosis.…”
Section: Level Of Evidencementioning
confidence: 99%
“…4,17,21 A systematic review of questionnaires that was used to assess patient satisfaction with any limb orthoses found that 63% of the 106 included papers used questionnaires that had been developed for the specific study rather than validated measures, indicating that our findings related to orthoses for knee instability is a broader issue in the field. 79 …”
Section: Findings In the Context Of Other Studiesmentioning
confidence: 99%
“…However, the focus was on gait biomechanics, and the effects and acceptability of long-term usage have not been evaluated. 21 A Cochrane review 22 has investigated any intervention for CMT disease and identified a single controlled study of foot orthoses (FOs); however, the device was not being used for knee instability -although FOs can influence the alignment of the knee on the coronal plane, they do not correct sagittal plane knee instability. A review of non-surgical interventions for people with CMT disease did not identify any studies evaluating an orthotic device.…”
Section: Previous Research On Effectivenessmentioning
confidence: 99%
“…Further research can help to identifythe best candidates for CF bracing by allowing for longitudinal use of the devices, thus allowing for motor learning in the orthoses. There is currently a dearth of literature with regards to muscle activity in orthoses due in large part to study design [17,18]. However, there is potential muscle activity can be enhance with proper orthosis selection [4].…”
Section: Discussionmentioning
confidence: 99%